Rapid plasma membrane-endosomal trafficking of the lymph node sinus and high endothelial venule scavenger receptor/homing receptor stabilin-1 (FEEL-1/CLEVER-1) - Prevo, Remko; Banerji, Suneale; Ni, Jian; Jackson, David G (The Journal of biological chemistry, 2004)
The sinusoidal endothelia of liver, spleen, and lymph node are major sites for uptake and recycling of waste macromolecules through promiscuous binding to a disparate family of scavenger receptors. Among the most complex is stabilin-1, a large multidomain protein containing tandem fasciclin domains, epidermal growth factor-like repeats, and a C-type lectin-like hyaluronan-binding Link module, which functions as an endocytic receptor for acetylated low density lipoprotein and advanced glycation end products. Intriguingly, stabilin-1 has also been reported to mediate both homing of leukocytes across lymph node high endothelial venules and adhesion of metastatic tumor cells to peritumoral lymphatic vessels. Currently, however, it is not clear how stabilin-1 mediates these distinct functions. To address the issue, we have investigated the tissue and subcellular localization of stabilin-1 in detail and assessed the functional status of its Link module. We show that stabilin-1 is almost entirely intracellular in lymph node high endothelial venules, lymphatic sinus endothelium, and cultured endothelial cells but that a finite population, detectable only by fluorescent antibody or fluorescein-labeled (Fl)-acetylated low density lipoprotein uptake, cycles rapidly between the plasma membrane and EEA-1+ve (early endosome antigen 1) early endosomes. In addition, we show using full-length stabilin-1 cDNA and a stabilin-1/CD44 chimera in HeLa cells that intracellular targeting is influenced by the transmembrane domain/cytoplasmic tail, which contains a putative dileucine (DXXLL) Golgi to endosomal sorting signal. Finally, we provide evidence that the stabilin-1 Link domain binds neither hyaluronan nor other glycosaminoglycans. These properties support a role for stabilin-1 as a rapidly recycling scavenger receptor and argue against a role in cell adhesion or lymphocyte homing.